2012
DOI: 10.1108/17465261211197421
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of corporate social responsibility to internal employee motivation

Abstract: Purpose -The purpose of this paper is to examine the impact of corporate social responsibility (CSR) on internal employee motivation. Design/methodology/approach -A survey was conducted among 274 employees from medium and large enterprises engaged in CSR activities in Lithuania. The research hypotheses were tested using correlation and regression analysis using factor scores from a principal component factor analysis.Findings -The findings suggest that internal and external CSR activities positively correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 42 publications
7
129
0
4
Order By: Relevance
“…Internal CSR practices refer to "CSR practices which are directly related with the physical and psychological working environment of employees" ( [32], p. 234). This focus on employees is due to the fact that they are considered very important internal stakeholders to the organization [44]. According to [45], internal CSR practices can be classified into four groups named "value classes".…”
Section: Internal Csrmentioning
confidence: 99%
“…Internal CSR practices refer to "CSR practices which are directly related with the physical and psychological working environment of employees" ( [32], p. 234). This focus on employees is due to the fact that they are considered very important internal stakeholders to the organization [44]. According to [45], internal CSR practices can be classified into four groups named "value classes".…”
Section: Internal Csrmentioning
confidence: 99%
“…There exists theoretical and empirical evidence to accept that this affirmation is valid (Aharon et al, 2011;Ali et al, 2010;Brammer et al, 2007;Galbreath, 2010;Kim et al, 2010;Skudiene and Auruskeviciene, 2012;Turker, 2009;Vitaliano, 2010); however, in the opinion of some authors, there is little evidence regarding the internal impact of CSR (Bolton et al, 2011;Rodrigo and Arenas, 2008;Wolf, 2013).…”
Section: Theoretical Background: Csr and Effectivenessmentioning
confidence: 99%
“…Bhattacharya et al (2008) found that management's top-down approach towards effective internal and external outcomes for the employees' satisfaction will produce strong elements of CSR in the organization. The close monitoring of internal CSR and employees' internal motivation can encourage the management to practically resolve the dilemmas by focusing on some areas of CSR (Skudiene & Auruskeviciene, 2012). Boyd and Gessner (2013) on the other hand argued that the metric system that is based on the management assessment alone is only focused on the organization's goals and interests; hence the partnership based on system is more applicable by considering employees' involvement in the performance metrics.…”
Section: Literature Review Corporate Social Responsibility and Stakehmentioning
confidence: 99%
“…When employees are passionate towards their work due to the great contribution given by their company, they will then make positive improvement in productivity and increase their commitment. Skudiene and Auruskeviciene (2012) further explained that the employees are more emotionally engaged to the organization due to their internal motivation grasped through sense of belonging and trust. The presence of employees' engagement can be attached with their contribution in decision making and reporting regardless of the type of CSR activities initiated.…”
Section: Corporate Social Responsibility and Employeementioning
confidence: 99%
See 1 more Smart Citation